Additional oligofructose/inulin does not increase faecal bifidobacteria in critically ill patients receiving enteral nutrition: A randomised controlled trial - Majid, Hazreen Abdul; Cole, Jayne; Emery, Peter W.; Whelan, Kevin (Elsevier, 2014)
Background & aims: Patients with diarrhoea during enteral nutrition (EN) have been shown to have low faecal bifidobacteria concentrations. Oligofructose/inulin selectively stimulate the growth of bifidobacteria in healthy humans. This study investigates the effect of additional oligofructose/inulin on the gastrointestinal microbiota, short-chain fatty acids (SCFA) and faecal output in patients receiving EN. Methods: Adult patients in the intensive care unit (ICU) who were starting EN with a formula containing fibre were randomised to receive 7 g/d of additional oligofructose/inulin or an identically packaged placebo (maltodextrin). A fresh faecal sample was collected at baseline and following at least 7 days of supplementation. Faecal microbiota were analysed using fluorescent in-situ hybridisation and faecal output was monitored daily. Results: Twenty-two patients (mean age 71 years) completed at least 7 days of intervention (mean 12 days). At the end of the intervention, there were no significant differences in the concentrations of bifidobacteria between the groups, after adjusting for baseline values (oligofructose/inulin 6.9 + 1.4, placebo 7.8 + 1.3 log(10) cells/g dry faeces, P > 0.05), but there were significantly lower concentrations of Faecalibacterium prausnitzii (7.0 + 1.0 vs. 8.4 + 1.3 log(10) cells/g, P = 0.01) and Bacteroides-Prevotella (9.1 + 1.0 vs. 9.9 + 0.9 logo cells/g, P = 0.05) in patients receiving additional oligofructose/inulin. There were no differences in faecal concentrations of any SCFA, secretory IgA, daily faecal score or incidence of diarrhoea between the two groups. Conclusions: Additional oligofructose/inulin did not increase faecal bifidobacteria in critically ill patients receiving EN, although it did result in lower concentrations of E prausnitzii and Bacteroides-Prevotella. (C) 2013 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism. All rights reserved.